Medical resarch and publication ethics - KASAPÇOPUR, Özgür (Cerrahpaşa Medical Journal, 2014)
Advances in the science of medicine and thus appearance of new inventions are only possible with scientific researches. Ethical rules that are ought to be followed during scientific researches have been formed throughout years. In this review, ethical rules about human researches and how they evolved are explained. Moreover, the ethical rules that should be regarded and violations of ethics while publishing new data acquired from scientific researches are also discussed in this article.